Waste liquid solidification agent and waste liquid solidification method
A sedimentation-type waste liquid solidifying agent with surface-crosslinked resin and cationic additives ensures rapid and uniform gelation, overcoming inefficiencies in existing technologies by minimizing agent use and adapting to varying waste liquid compositions.
Patent Information
- Application Number
- JP2021502218
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-22
- Filing Date
- 2020-02-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-02-21
AI Technical Summary
Existing waste liquid solidifying agents, both sedimentation and floating types, face challenges in uniformly and quickly gelling waste liquids with varying compositions, often requiring excessive amounts and being cost-inefficient due to fluctuating solidification times and uneven gelation.
A sedimentation-type waste liquid solidifying agent comprising surface-crosslinked water-absorbing resin powder with a water-insoluble cationic additive, allowing for rapid and uniform gelation by adjusting the amount based on waste liquid composition.
The agent quickly and uniformly gels waste liquids with minimal added quantity, addressing composition variability and reducing costs by enabling precise addition based on waste liquid concentration.
Smart Images

Figure 0007605731000003 
Figure 0007605731000004 
Figure 0007605731000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a particulate waste liquid solidifying agent containing a water-absorbent resin and a waste liquid solidifying method using the waste liquid solidifying agent. More specifically, the present invention relates to a particulate waste liquid solidifying agent that uniformly solidifies waste liquid, further aqueous waste liquid mainly composed of water, particularly medical waste liquid containing blood or body fluids, and shortens the solidification time, and to the waste liquid solidifying method. [Background technology]
[0002] The amount of waste liquid discharged from various industrial fields is steadily increasing. Examples of waste liquid (aqueous waste liquid) include factory waste liquid, waste liquid generated in food processing such as meat and fish, radioactive waste liquid, beverage waste liquid, waste liquid containing sludge, bodily fluid waste liquid such as urine and phlegm, blood discharged from dental treatments and hospital operations, and medical waste liquid such as amniotic fluid and blood discharged during childbirth. Conventionally, in order to safely dispose of such waste liquid, it has been collected in containers and then incinerated or treated with chemicals before being disposed of in a septic tank.
[0003] However, if waste liquid is stored or transported in a liquid state, there is a risk of secondary contamination due to damage to the waste liquid container or scattering of the waste liquid. For this reason, methods of solidifying (also called gelling) waste liquid, especially medical waste liquid, have been proposed. For example, water-absorbent resins (also known as superabsorbent polymers) have been proposed as a gelling agent for waste liquid (Patent Documents 1 to 13). Water-absorbent resins are used in many applications, mainly in disposable diapers (Non-Patent Documents 1 and 2), and one of the various applications of water-absorbent resins has been proposed as a waste liquid solidifying agent.
[0004] Specifically, for efficient solidification of waste liquid, there have been proposed waste liquid solidification agents and waste liquid solidification methods using water-absorbent resins, such as the addition of surfactants (Patent Documents 1-4, 11), the addition of inorganic particles such as silica (Patent Documents 5-8), the addition of hydrophobic substances such as metal soaps (Patent Documents 8, 9), the addition of alkali-soluble resins to water-absorbent resins (Patent Document 10), the combined use of anionic water-absorbent resins such as polyacrylates and nonionic water-absorbent resins (Patent Document 12), and a method using a water-absorbent resin and a chelating agent (Patent Document 13).
[0005] In these Patent Documents 1 to 13, the water-absorbent resin has a specific gravity (for example, a sodium polyacrylate-based water-absorbent resin has a specific gravity of about 1.6 g / cm 3 Generally, waste liquid (water-based waste liquid with a specific gravity of about 1.0 g / cm 3 The waste liquid solidifying agent that settled in the waste liquid gradually swells and gels from the lower part of the waste liquid, gelling the entire waste liquid (hereinafter referred to as a sedimentation type waste liquid solidifying agent). However, when the container for storing the waste liquid is a vertically long cylindrical container (height of 10-odd centimeters to several meters), the sedimentation type waste liquid solidifying agent requires a long time for the water absorbent resin that has once settled to swell in the vertical direction (10-odd centimeters to several meters). Furthermore, the water absorbent resin that settled in the container swells from the lower part, gradually swelling to the middle part of the container and finally to the upper part of the container. Therefore, when the amount of water absorbent resin near the upper part of the container is insufficient compared to the lower part, the gelation of the upper part of the waste liquid tends to be insufficient. As a result, the gel at the upper part of the container tends to flow easily even after the waste liquid gels.
[0006] In order to solve this problem, a waste liquid solidification agent has been proposed that does not settle in the waste liquid as with conventional settling-type waste liquid solidification agents, but rather gels the waste liquid from both the top and bottom by, for example, making the water-absorbing resin hydrophobic, so that part of the waste liquid solidification agent floats in the waste liquid and the other part settles, thereby gelling the waste liquid quickly and uniformly (hereinafter referred to as a floating-type waste liquid solidification agent; Patent Documents 8, 9, and 11).
[0007] However, in the floating type waste liquid solidifying agent described in Patent Documents 8, 9, and 11, which gels the waste liquid from both the top and bottom of the waste liquid, the floating rate is affected by the composition (ingredients and concentration) of the waste liquid, so there is a problem that the solidification time and gelation state vary. Furthermore, depending on the composition of the waste liquid (e.g., salt concentration, blood concentration, etc.), the floating type waste liquid solidifying agent may completely float on the waste liquid and solidification may not proceed. With such a floating type waste liquid solidifying agent, the top and bottom of the waste liquid in the container gel at the same time, and finally the middle of the container (the center part in the case of a vertically long container) gels. Therefore, if the amount of waste liquid solidifying agent added to the waste liquid is insufficient and the gelation of the middle part is insufficient, it is difficult to add additional waste liquid solidifying agent because the upper part of the waste liquid has already gelled (solidified). Generally, the composition of waste liquid (for example, the salt concentration or blood concentration that inhibits the swelling of the water-absorbing resin) is different each time, so not only does the floating rate change, but the amount of water-absorbing resin required to solidify the waste liquid is different each time. Therefore, when using a floating type waste liquid solidifying agent in practice, in order to completely solidify the entire waste liquid regardless of the waste liquid composition, it was necessary to add an excessive amount of waste liquid solidifying agent relative to the amount of waste liquid. The need to add such an excess of waste liquid solidifying agent allows for rapid and uniform gelation of the waste liquid, but floating type waste liquid solidifying agents are disadvantageous in terms of cost.
[0008] On the other hand, with conventional sedimentation type waste liquid solidifying agents, the gelation time is still slow even after additional addition, and the gel ratio of the upper layer is low, so excessive addition of the waste liquid solidifying agent is necessary. Therefore, there has been a demand for a waste liquid solidifying agent that can gel the entire waste liquid quickly and uniformly with the minimum amount added, according to the composition of the waste liquid, which changes each time. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2017-125132 A [Patent Document 2] JP 2016-136133 A [Patent Document 3] JP 2015-052091 A [Patent Document 4] JP 2009-167371 A [Patent Document 5] Japanese Patent Application Publication No. 04-235783 [Patent Document 6] Japanese Patent Application Publication No. 06-000216 [Patent Document 7] Japanese Patent Application Publication No. 08-047637 [Patent Document 8] JP 2016-203106 A [Patent Document 9] WO2005 / 107940 publication [Patent Document 10] JP 2006-143972 A [Patent Document 11] WO2005 / 024039 publication [Patent Document 12] JP 2002-119853 A [Patent Document 13] Japanese Patent Application Publication No. 11-169451 [Non-patent literature]
[0010] [Non-Patent Document 1] Modern Superabsorbent Polymer Technology(1988),page69-103,pages251-272 [Non-Patent Document 2] Superabsorbent Polymers New Polymer Materials One Point-4 Edited by Society of Polymer Science Fusayoshi Masuda Kyoritsu Shuppan, p81-110 [Non-Patent Document 3] NONWOVENS STANDARD PROCEDURES(2015) Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in consideration of the above-mentioned problems with floating-type and sinking-type waste liquid solidifying agents. The object of the present invention is to provide a waste liquid solidifying agent that can quickly and uniformly gel the entire waste liquid with less addition amount than conventionally, preferably the minimum necessary amount, in accordance with the composition of the waste liquid, which changes each time. [Means for solving the problem]
[0012] In order to solve the above problems, the present inventors conducted extensive research and found that the above problems can be solved by using a cationic additive on the surface of a surface-crosslinked water-absorbent resin instead of the additives of the conventional waste liquid solidifying agents described in Patent Documents 1 to 13 (surfactants, inorganic particles, chelating agents, nonionic water-absorbent resins, alkali-soluble resins, hydrophobic substances, etc.), and that a sedimentation-type waste liquid solidifying agent can be used for the first time to rapidly and uniformly gel the waste liquid, thereby completing the present invention.
[0013] (Waste liquid solidification agent of the present invention) That is, in order to solve the above problems, the waste liquid solidifying agent of the present invention contains a water absorbent resin composition including (A) a surface-crosslinked water absorbent resin powder and (B) a water-insoluble cationic additive present on the surface of the surface-crosslinked water absorbent resin powder.
[0014] (Method of solidifying waste liquid according to the present invention) In order to solve the above problems, the present invention provides a method for solidifying a waste liquid using the above waste liquid solidifying agent.
[0015] (Method of Disposing of Waste Liquid of the Present Invention) In order to solve the above problems, the present invention provides a method for disposing of waste liquid, in which the waste liquid solidified by the above method for solidifying waste liquid is disposed of together with the container.
[0016] (Waste liquid solidification agent package of the present invention) In order to solve the above problems, there is provided a waste liquid solidifying agent package in which any of the above waste liquid solidifying agents is packaged in a water-insoluble container having a discharge outlet. Effect of the Invention
[0017] The present invention is a sedimentation type waste liquid solidifying agent that can gel the waste liquid quickly and uniformly in the upper and lower layers, and can be easily added according to the concentration of the waste liquid. Therefore, it is only necessary to add the waste liquid solidifying agent appropriately until the upper part of the waste liquid gels according to the composition of the waste liquid, which changes each time, and the entire waste liquid can be gelled quickly and uniformly with the minimum amount of waste liquid solidifying agent added each time. With a floating type waste liquid solidifying agent, it is difficult to adjust the amount of waste liquid solidifying agent added according to the composition of the waste liquid, which changes each time, or to add more if the amount added is insufficient. In contrast, with a sedimentation type waste liquid solidifying agent, even if the amount added to the waste liquid is insufficient, the upper part remains as waste liquid, so it is relatively easy to add more waste liquid solidifying agent to make up for the shortage as needed. Furthermore, the sedimentation type waste liquid solidifying agent does not have the problem that the floating rate that governs the solidification time changes each time depending on the waste liquid composition, as with a floating / settling type waste liquid solidifying agent. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a diagram showing a method for evaluating the gel fluidity of the waste liquid solidifying agent of the present invention. [Diagram 2] FIG. 1 shows the top layer (approximately 200 ml) and bottom layer (approximately 200 ml) of a 1000 ml measuring cylinder in the measurement of the top and bottom gel magnification. [Diagram 3] FIG. 13 is a diagram showing a floating-type waste liquid solidifying agent in a state where the central portion 8 of a 1000 ml graduated cylinder is not gelled (excess water in the central portion). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] An embodiment of the present invention will be described below, but the present invention is not limited thereto. In order to solve the above problems, the present invention provides a waste liquid solidifying agent containing a water absorbent resin composition including (A) a surface-crosslinked water absorbent resin powder and (B) a water-insoluble cationic additive present on the surface of the water absorbent resin powder. The present invention will be further described below.
[0020] (1) Water absorbent resin, water absorbent resin powder The water-absorbent resin refers to a water-swellable, water-insoluble crosslinked polymer capable of forming a hydrogel, and has a water absorption capacity (CRC) (NWSP241.0.R2(15)) as specified in Non-Patent Document 3 of 5 g / g or more, and an extractables (NWSP270.0.R2(15)) as specified in Non-Patent Document 3 of 0 to 50 mass%, more preferably 0 to 25 mass%, even more preferably 0 to 20 mass%, particularly preferably 0 to 15 mass%, and most preferably 0 to 10 mass%. Incidentally, "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015" in Non-Patent Document 3, which was jointly published by EDANA (European Disposables And Nonwovens Association) and INDA (Association of the Nonwoven Fabrics Industry) to standardize evaluation methods for nonwoven fabrics and their products in the United States and Europe, and indicates standard measurement methods for water-absorbent resins.
[0021] The method for producing the water-absorbent resin is not limited, and various known production methods can be adopted. For example, as described in Non-Patent Document 1, Chapter 3, p. 69-101 and Patent Document 8, the water-absorbent resin can be obtained by polymerizing an aqueous monomer solution containing a crosslinking agent with a radical polymerization initiator and drying the hydrogel after polymerization. In addition, the water-absorbent resin of the present invention can be appropriately produced by the methods described in Non-Patent Document 1 and Patent Documents 1 to 12 (particularly Patent Documents 8 and 9). This will be explained in more detail below.
[0022] In the present invention, from the viewpoint of absorption characteristics, one or a mixture of water-absorbing resins having a crosslinked structure obtained by polymerizing a water-soluble ethylenically unsaturated monomer is essentially used as the water-absorbing resin. From the viewpoints of cost and waste liquid solidification performance, the water-absorbing resin is preferably a water-absorbing resin obtained from a water-soluble ethylenically unsaturated monomer containing an acid group, particularly a carboxyl group, and more preferably a crosslinked polyacrylic acid partially neutralized product obtained by polymerizing and crosslinking a monomer mainly composed of acrylic acid and / or its salt (neutralized product) (hereinafter, a mixture of acrylic acid and / or its salt (neutralized product) is referred to as acrylic acid (salt), and a crosslinked polyacrylic acid partially neutralized product is sometimes referred to as a polyacrylic acid (salt)-based crosslinked polymer). When acrylic acid (salt) is used in the present invention, the monomer other than the acrylic acid (salt) is preferably 0 to 30 mol %, more preferably 0 to 10 mol %, based on the total amount of acrylic acid and its salt used as the main component. Within this range, in addition to an appropriate gelation time, other functions such as antibacterial properties and deodorization properties can be imparted, and the waste liquid solidifying agent can be obtained at a lower cost. As monomers other than acrylic acid, acid group-containing unsaturated monomers such as 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acryloxyalkanesulfonic acid and their alkali metal salts and ammonium salts, N-vinyl-2-pyrrolidone, N-vinylacetamide, (meth)acrylamide, etc. can be appropriately used. The water-absorbing resin that can be suitably used in the waste liquid solidifying agent of the present invention is a water-absorbing resin mainly composed of a polyacrylic acid (salt)-based crosslinked polymer.
[0023] The neutralization rate of the acid groups contained in the water absorbent resin (mol % of neutralized acid groups among all acid groups) is preferably 10 to 100 mol %, more preferably 30 to 90 mol %, and further preferably 40 to 80 mol %. To form the above salt, the monomer may be neutralized, or a non-neutralized monomer may be mixed with a neutralized monomer, or the monomer may be neutralized as a polymer during or after polymerization, or these may be used in combination. In addition, the description of the numerical range of the present invention, for example, the description of AA to AA, preferably BB to BB, more preferably CC to CC, and further preferably DD to DD (alphabet represents a number), can be appropriately combined to select the upper and lower limits. For example, the numerical range can be set by selecting the upper and lower limits arbitrarily from a combination of suitable ranges, such as AA to BB or CC to BB (hereinafter, this applies to the description of the numerical range). In addition, in this specification, "mass" and "weight", "parts by mass" and "parts by weight", "% by mass" and "% by weight", "ppm by mass" and "ppm by weight" are treated as having the same meaning. The unit of volume "liter" may be written as "l" or "L". "% by mass" may be written as "wt%".
[0024] The water absorbent resin of the present invention is a crosslinked body, and an internal crosslinking agent is preferably used during polymerization. Specific examples of the internal crosslinking agent include N,N'-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, triallylamine, poly(meth)acryloxyalkane, (poly)ethylene glycol diglycidyl ether, pentaerythritol, ethylenediamine, and ethylene carbonate. The amount of these internal crosslinking agents used is preferably within the range of 0.001 to 2 mol%, more preferably 0.005 to 0.5 mol%, further preferably 0.01 to 0.2 mol%, and particularly preferably 0.03 to 0.15 mol% relative to the monomer (excluding the internal crosslinking agent) in terms of physical properties.
[0025] The water-absorbing resin of the present invention is obtained by polymerizing an aqueous solution of a monomer (hereinafter referred to as an aqueous monomer solution). The concentration of the monomer in the aqueous monomer solution is determined depending on the temperature of the aqueous solution and the monomer, and is not particularly limited, but is preferably 10 to 70% by mass, more preferably 20 to 60% by mass. In addition, the aqueous monomer solution may be used in combination with a solvent other than water as necessary, and the type of the solvent used in combination is not particularly limited. Furthermore, the crosslinked body obtained by polymerization is dehydrated, dried, and pulverized as necessary by the method described in the above-mentioned patent documents, etc., to obtain a water-absorbing resin powder.
[0026] The water absorbent resin of the present invention is usually dried at a temperature in the range of 60 to 250° C., preferably 100 to 220° C., and more preferably 120 to 200° C. The drying time depends on the surface area of the crosslinked body, the moisture content, and the type of dryer, and is selected so as to achieve a desired moisture content.
[0027] The moisture content of the water absorbent resin powder (composition) that can be used in the present invention (defined as the amount of moisture contained in the water absorbent resin or waste liquid solidifying agent / measured as the loss on drying of 1 g of the water absorbent resin or waste liquid solidifying agent at 180°C for 3 hours) is not particularly limited, but is more preferably 0.2 to 30 mass%, further preferably 0.3 to 15 mass%, and particularly preferably 0.5 to 10 mass%. The water absorbent resin powder of the present invention is a powder that exhibits fluidity even at room temperature from the viewpoint of performance as a waste liquid solidifying agent. The preferred particle size of the water absorbent resin powder (and the water absorbent resin composition) will be described later.
[0028] (2) Surface-crosslinked water-absorbent resin powder The waste liquid solidifying agent of the present invention essentially uses a surface-crosslinked water-absorbent resin powder. If the water-absorbent resin used in the waste liquid solidifying agent is not surface-crosslinked, the rapid and uniform gelling of the waste liquid (gelling of the waste liquid into a substantially non-fluid gel), which is the object of the present invention, cannot be achieved.
[0029] The water-absorbent resin used in the waste liquid solidifying agent of the present invention is subjected to the above-mentioned crosslinking polymerization and drying (or partial drying), and if necessary, pulverized, and further subjected to a surface crosslinking (secondary crosslinking) treatment.
[0030] There are various types of surface crosslinking agents for crosslinking the above-mentioned surface, and from the viewpoint of physical properties, polyhydric alcohol compounds, epoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, mono-, di-, or polyoxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, etc. can be used. Specific examples of the surface crosslinking agents used in the present invention are exemplified in Patent Documents 8 and 9, U.S. Patent Nos. 6,228,930, 6,071,976, and 6,254,990. For example, polyhydric alcohol compounds such as mono-, di- or poly-ethylene glycol, propylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, glycerin, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol, epoxy compounds such as mono-, di- or poly-ethylene glycol diglycidyl ether and glycidol, oxazolidinone compounds such as 2-oxazolidinone, and alkylene carbonate compounds such as ethylene carbonate, are included, but are not particularly limited. In order to maximize the effects of the present invention, it is preferable to use at least a polyhydric alcohol among these crosslinking agents, and polyhydric alcohols having 2 to 10 carbon atoms, preferably 3 to 8 carbon atoms, are more preferably used.
[0031] The amount of the surface cross-linking agent used is usually 0.001 to 10 parts by mass, preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water absorbent resin. In the present invention, when the surface cross-linking agent is added, it is preferable to use water, and it is preferable to add and mix an aqueous solution of the surface cross-linking agent to the water absorbent resin. In this case, the amount of water used is in the range of 0.5 to 20 parts by mass, preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water absorbent resin. In addition, in the present invention, a hydrophilic organic solvent may be used other than water. The amount of the hydrophilic organic solvent is in the range of 0 to 10 parts by mass, preferably 0 to 5 parts by mass, more preferably 0 to 3 parts by mass, relative to the water absorbent resin.
[0032] In addition, in the case where a water absorbent resin is obtained by reversed phase suspension polymerization, a water absorbent resin having a crosslinked surface can be obtained by dispersing the above-mentioned surface crosslinking agent in a hydrophobic organic solvent during azeotropic dehydration and / or at the end of azeotropic dehydration after the completion of polymerization, for example, at a water content of the water absorbent resin of 5 to 50 mass%, preferably 5 to 40 mass%, more preferably 5 to 30 mass%.
[0033] The water absorbent resin after mixing with the surface cross-linking agent is preferably heat-treated. Conditions for the heat treatment include a temperature of the water absorbent resin or a heat medium temperature of usually 60 to 280° C., preferably 100 to 250° C., more preferably 150 to 240° C., and a heating time of preferably 1 minute to 2 hours.
[0034] (3) Cationic additives The waste liquid solidifying agent of the present invention contains a water absorbent resin composition. The water absorbent resin composition contains (A) a surface-crosslinked water absorbent resin powder and (B) a water-insoluble cationic additive present on the surface of the water absorbent resin powder. The water absorbent resin composition of the present invention preferably contains (B) a water-insoluble cationic additive essentially on the surface of (A) the surface-crosslinked water absorbent resin powder (2). The phrase "containing" a water-insoluble cationic additive on the surface of the water absorbent resin powder or "existing" a water-insoluble cationic additive means that the cationic additive is present on the surface of the water absorbent resin powder, such as a state in which the cationic additive is attached to the surface of the water absorbent resin powder or a state in which a part of the cationic additive incorporated inside the water absorbent resin powder appears on the surface of the water absorbent resin powder. The cationic additive may be present on at least a part of the surface of the water absorbent resin powder, and may preferably be localized near the surface. The state of existence of the water-insoluble cationic additive can be confirmed by fluorescent X-rays. Specifically, the amount of metal cations in a water absorbent resin composition can be measured by fluorescent X-ray analysis, and by measuring a water absorbent resin powder which has been subjected to pretreatment such as pulverization or grinding as necessary, it can be confirmed that a water insoluble cationic additive is present on a surface of a water absorbent resin powder.
[0035] In addition, the water absorbent resin composition contained in the waste liquid solidifying agent of the present invention is preferably configured such that (A) the surface-crosslinked water absorbent resin powder is the main component, and (B) the surface of the water absorbent resin powder contains a water-insoluble cationic additive. The surface-crosslinked water absorbent resin powder is the main component, and the content of the water absorbent resin powder in the water absorbent resin composition is 50 to less than 100 mass%, preferably 70 to 99 mass%, and more preferably 80 to 98 mass%, and the cationic additive is contained as a component other than the water absorbent resin powder. The water absorbent resin composition is preferably configured by the water absorbent resin composition and the water-insoluble cationic additive, but may contain the additives described in the following (4-1) as other components.
[0036] The waste liquid solidifying agent of the present invention essentially uses a surface-crosslinked water-absorbent resin powder and a water-insoluble cationic additive. If a cationic additive is not used, the problem of the present invention, rapid and uniform gelation of waste liquid (effectively gelation of waste liquid into a non-fluid gel), cannot be achieved for a sedimentation type waste liquid solidifying agent. In the present invention, instead of the conventional additives described in Patent Documents 1 to 13, a water-insoluble cationic additive is used in the surface-crosslinked water-absorbent resin powder, so that the waste liquid solidifying agent can be precipitated and rapidly and uniformly gelled. Therefore, a waste liquid solidifying agent that rapidly and uniformly gels the entire waste liquid with the minimum necessary amount of addition can be provided according to the composition of the waste liquid, which changes each time.
[0037] (3-1) Water-insoluble cationic additives (Cation) In order to solve the problems of the present invention, the cationic additive in the present invention may be a compound containing a specific cation, preferably a compound containing a trivalent or higher metal cation, typically an aluminum cation. The cationic additive is an inorganic additive containing an aluminum cation, and the counter anion may be either an organic anion or an inorganic anion, but preferably a cationic inorganic additive is used which is an inorganic compound having an inorganic anion as a counter anion.
[0038] (Solubility) In order to solve the problems of the present invention, the cationic additive is water-insoluble. In addition, water-insoluble includes poor water solubility, specifically, the solubility of the additive in water (23°C) is 10g / 100g water or less, preferably 5g / 100g water or less, more preferably 1g / 100g water or less, and more preferably 0.1g / 100g water or less. In addition, the water-insoluble cationic additive is preferably cationic fine particles. The water-insoluble cationic fine particles may be in a water-dispersed state including a colloidal state (sol) or a slurry state, and may be dispersed in water with a surfactant or dispersant as necessary. Cationic colloidal silica and the like are preferably used as the water-insoluble cationic fine particles.
[0039] (particle size) In order to solve the problems of the present invention, when the cationic additive is used as fine particles, the particle size is preferably 50 μm or less, 30 μm or less, 10 μm or less, 5 μm or less, 2 μm or less, and 1 μm or less, in that order. The lower limit is about 10 nm. The particle size of the cationic additive, particularly the volume average particle size, can be measured by the "laser diffraction scattering method" (for example, using a particle size analyzer manufactured by Nikkiso Co., Ltd., trade name: Microtrac MT3000II).
[0040] (Typical cationic additives) The cationic additives preferably used in the present invention include one or more inorganic fine particles selected from cationic colloidal silica, hydrotalcite, zeolite, and aluminum salt. As these cationic additives, cationic colloidal silica, hydrotalcite, and zeolite are particularly preferred. In addition, it is preferable that the cationic additives are positively charged, and as the cationic additives positively charged, cationic colloidal silica and hydrotalcite can be preferably used. These can be used alone or in combination of two or more. In addition, when multiple examples are given in the following specific examples, one or more can be used in combination.
[0041] (cationic colloidal silica) As the cationic colloidal silica, cationic colloidal silica in which the surface of silicon dioxide particles is coated with aluminum ions can be used. As the cationic colloidal silica, it is preferable that the particles are positively charged by being coated with aluminum ions. In addition, it is preferable that the cationic colloidal silica has a positive zeta potential, usually +60 mV or less, preferably in the range of +5 to +55 mV. The method for producing such cationic colloidal silica is not particularly limited, but may be a known method, such as the method described in JP-A-2-172812.
[0042] The method for cationizing the cationic colloidal silica is not particularly limited. A common method is to react a compound of a polyvalent metal ion such as an aluminum ion to coat the surface of the colloidal silica with the aluminum ion, but a silane coupling agent having an ammonium group may be added to the surface of the colloidal silica to modify it into cationic colloidal silica.
[0043] The colloidal silica is also available as a commercially available product, and preferred examples of the product include Klebosol 20H12, Klebosol 30CAL25, and Klebosol 30CAL manufactured by Merck.
[0044] (Hydrotalcite) Hydrotalcite is a multi-element metal compound containing two types of metal cations, divalent and trivalent, and a hydroxyl group, and is represented by the following general formula (1): TIFF0007605731000001.tif6133(1)
[0045] (M1 2+ is a divalent metal cation, M 3+ is a trivalent metal cation, A n-It is a structure of a layered compound represented by (where is an n-valent anion and H2O represents water), and since divalent metal cations are partially replaced by trivalent metal cations, its host layer is known to be positively charged. The ratio of the divalent metal cation to the trivalent metal cation in the general formula (1) is preferably in the range of x = 0.2 to 0.75, more preferably in the range of 0.25 to 0.7, and even more preferably in the range of 0.25 to 0.5. Also, as the anion, OH - 、F - 、Cl - 、Br - 、NO3 - 、CO3 2- 、SO4 2- 、Fe(CN)6 3- 、CH3COO - 、oxalate ion or salicylate ion etc. can be mentioned, but carbonate anion is preferred. Also, m is a real number greater than 0, and it is preferably 0 < m ≤ 10.
[0046] The shape is not particularly limited, but it is preferably spherical (including powdery). Also, it is preferably of a certain particle size, and the volume average particle diameter is preferably 2 μm or less, more preferably 1.5 μm or less, and even more preferably 1 μm or less. When the particle diameter becomes large, it is necessary to increase the addition amount in order to show rapid and uniform solidification of the waste liquid, which is the problem of the present invention. As a result, the performance of the obtained waste liquid solidifying agent may be impaired. If it is too small, the workability during the addition process may decrease or there is a risk of not obtaining sufficient performance. Therefore, the volume average particle diameter is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more. Furthermore, an organic compound may be intercalated between the layers, or a surface treatment may be performed to enhance the miscibility with a water-absorbing resin or the like.
[0047] As a preferred structural formula of hydrotalcite, Mg6Al2(OH) 16 CO3·4H2O or Mg4Al2(OH) 12Specific examples include DHT-4H and DHT-6 manufactured by Kyowa Chemical Industry Co., Ltd., and STABIACE HT-1-NC and STABIACE HT-P manufactured by Sakai Chemical Industry Co., Ltd.
[0048] (Zeolite) Zeolite is a crystalline hydrous aluminosilicate having a network structure in which SiO4 and AlO4 tetrahedra (hereinafter collectively referred to as TO4 tetrahedra) share apical oxygen atoms and are connected infinitely in three dimensions. The zeolite that can be used in the present invention is sufficient if it contains aluminum cations. Both natural and synthetic zeolites can be used, but synthetic zeolites that are commercially available and stable are preferred. Specifically, for example, A-type zeolite (Na 12 (AlO2) 12 (SiO2) 12 ·27H2O), X-type zeolite zeolite (Na 86 (AlO2) 86 (SiO2) 106 264H2O), Y-type zeolite (Na 56 (AlO2) 56 (SiO2) 136 ·250H2O), L-type zeolite (K9(AlO2)9(SiO2) 27 ·22H2O), Omega type zeolite (Na 6.8 TMA 1.6 (AlO2)8(SiO2) 28 ·21H2O, TMA:tetramethyl-ammonium), ZSM-5((Na,TPA)3(AlO2)3(SiO2) 93 16H2O, TPA: tetrapropyl-ammonium), etc.
[0049] (aluminum salts) As the water-insoluble cationic fine particles of the present invention, an aluminum salt can also be used. As the water-insoluble aluminum salt, at least one selected from the group consisting of aluminum lactate, aluminum hydroxide, and aluminum phosphate can be used. These aluminum salts may be used as powders, or may be used as a slurry or powders prepared by reacting a precursor in water to prepare an aqueous dispersion.
[0050] (3-2) Content of cationic additive In the water absorbent resin composition of the present invention, the amount of the cationic additive added is preferably 0.01 to 5 mass %, more preferably 0.01 to 4.5 mass %, further preferably 0.1 to 4.5 mass %, further more preferably 0.1 to 4 mass %, and particularly preferably 0.15 to 3.5 mass %, based on the surface-crosslinked water absorbent resin powder. If the amount of the water-insoluble cationic additive added is less than 0.01% by mass, a sufficient effect may not be obtained in terms of rapid and uniform solidification of the waste liquid, and even if it is added in an amount exceeding 5% by mass, an effect commensurate with the amount added cannot be obtained.
[0051] (4) Waste liquid solidification agent containing a water-absorbing resin composition The waste liquid solidifying agent of the present invention preferably contains a surface-crosslinked water absorbent resin powder as a main component, the content of the water absorbent resin powder in the waste liquid solidifying agent is 50 to less than 100 mass%, preferably 70 to 99 mass%, and further preferably 80 to 98 mass%, and the above-mentioned cationic additive is used as a component other than the water absorbent resin powder.
[0052] (4-1) Other additives In addition to the water-insoluble cationic additive, the waste liquid solidifying agent of the present invention may further preferably contain a water-soluble cationic polyvalent metal additive such as a water-soluble aluminum salt (a water-soluble cationic polyvalent metal additive whose solubility in water is equal to or greater than that of the insoluble cationic additive) from the viewpoint of liquid permeability in order to further solve the problems of the present invention. It is also preferable that the waste liquid solidifying agent contains water. In addition, it may further contain additives that impart various functions, such as deodorants, antibacterial agents, fragrances, foaming agents, pigments, dyes, plasticizers, adhesives, surfactants, fertilizers, oxidizing agents, protein crosslinking agents, reducing agents, water, salts, chelating agents, disinfectants, hydrophilic polymers such as polyethylene glycol and polyethyleneimine, and thermosetting resins such as polyester resins and urea resins, as necessary.
[0053] The amount of additives (for example, water) other than these water-insoluble cationic additives used is usually 0 to 30 parts by mass, preferably in the range of 0 to 10 parts by mass, and more preferably in the range of 0 to 1 part by mass, relative to 100 parts by mass of the water absorbent resin powder.
[0054] (4-2) Manufacturing method of waste liquid solidification agent The method for producing a waste liquid solidifying agent of the present invention is a method for producing a particulate waste liquid solidifying agent essentially comprising a water-absorbent resin powder having a crosslinked structure obtained by polymerizing a water-soluble ethylenically unsaturated monomer, and the cationic additive is mixed into the water-absorbent resin powder either before, during, or after surface crosslinking, thereby making the cationic additive present on the surface of the surface-crosslinked water-absorbent resin.
[0055]
[0213] When the cationic additive used in the present invention is a powder, for example, a method of directly mixing the powder as it is with any of water absorbent resin powders before surface crosslinking, during surface crosslinking, and after surface crosslinking, a method of dispersing the cationic additive in a surface crosslinking agent solution in which the above-mentioned surface crosslinking agent, water, and if necessary, a hydrophilic organic solvent are mixed, and mixing the cationic additive in a slurry state with a water absorbent resin powder, or a method of dispersing the cationic additive in water or a hydrophilic organic solvent in a slurry state with a water absorbent resin before surface crosslinking, during surface crosslinking, and after surface crosslinking, is used.
[0056] When the cationic additive is dispersed in a slurry state and mixed with the water absorbent resin powder, the amount of water or the aqueous dispersion containing water and a hydrophilic organic solvent, etc., which is used as necessary, varies depending on the type and particle size of the water absorbent resin, but in general, in the case of water, it is 10 parts by mass or less, preferably 1 to 5 parts by mass, relative to 100 parts by mass of the solid content of the water absorbent resin powder. Similarly, the amount of the hydrophilic organic solvent used is usually 10 parts by mass or less, preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the solid content of the water absorbent resin powder. The concentration of the cationic additive in the slurry is appropriately selected depending on the type of the additive and the dispersion solvent used, and the viscosity of the slurry, and is not particularly limited, but is usually 0.001 to 30% by mass, preferably 0.01 to 10% by mass. The powder temperature of the water absorbent resin when mixed with the cationic additive is usually room temperature or higher, but in order to obtain stable liquid absorption characteristics and fluidity during moisture absorption of the particulate waste liquid solidifying agent, it is preferably mixed at 40 to 180°C, more preferably 50 to 100°C.
[0057] In the present invention, a device used when mixing a water absorbent resin powder with a liquid, powder and / or slurry solution containing a cationic additive may be a known device, and examples thereof include a cylindrical mixer, a screw mixer, a screw extruder, a turbulizer, a Nauter mixer, a V-type mixer, a ribbon mixer, a double-arm kneader, a fluid mixer, an airflow mixer, a rotating disk mixer, a roll mixer, a rolling mixer, etc., and the speed at the time of mixing may be high or low. Note that these mixers can also be used for mixing a surface crosslinking agent at the time of performing surface crosslinking of the above-mentioned water absorbent resin.
[0058] (5) Properties of Water-Absorbent Resin and Water-Absorbent Resin Composition In order to solve the problems of the present invention, it is preferable that the surface-crosslinked water absorbent resin powder, the water absorbent resin composition, and the waste liquid solidifying agent containing the water absorbent resin composition of the present invention (hereinafter, commonly referred to as "waste liquid solidifying agent" in (5-1) to (5-6)) further satisfy the following physical properties. Hereinafter, representative physical properties can be specified in Non-Patent Document 3, NONWOVENS STANDARD PROCEDURES (2015), and similar measurement methods are also described in Patent Documents 8 and 9.
[0059] (5-1) CRC(NWSP241.0.R2(15)) The absorption capacity (CRC) of the waste liquid solidifying agent of the present invention is usually 10 g / g or more, preferably 25 g / g or more, more preferably 30 g / g or more, and even more preferably 33 g / g or more for physiological saline. There is no particular upper limit, but usually about 100 g / g or about 50 g / g is sufficient. It is preferably adjusted to the range of 25 to 50 g / g. When the absorption capacity (CRC) is low, a large amount of solidifying agent is required and the solidification time is also long. As described above, the absorption capacity (CRC) can be set to the above range by appropriately adjusting the internal crosslinking and surface crosslinking of the water-absorbing resin.
[0060] (5-2)AAP(Absorption Against Pressure)(NWSP242.0.R2(15)) The absorption capacity under pressure (AAP0.3) of the waste liquid solidifying agent of the present invention is preferably 15 to 40 g / g, and the absorption capacity under pressure (AAP0.7) is preferably 10 to 35 g / g.
[0061] The absorbency under pressure (AAP0.3) (absorbency after 0.9 g of the absorbent resin is swollen for 1 hour under a load of 2.06 kPa in a 0.9% by mass aqueous sodium chloride solution) is preferably 24 [g / g] or more, more preferably 26 [g / g] or more, even more preferably 28 [g / g] or more, and most preferably 30 [g / g] or more. The upper limit of AAP0.3 is not particularly limited, but in terms of the balance with other physical properties, it is preferably 40 [g / g] or less, more preferably 38 [g / g] or less, and even more preferably 35 [g / g] or less.
[0062] The absorbency under pressure (AAP0.7) (absorbency after 0.9 g of the absorbent resin is swollen in a 0.9% by mass aqueous sodium chloride solution under a load of 4.83 kPa for 1 hour) is preferably 20 [g / g] or more, more preferably 22 [g / g] or more, and even more preferably 24 [g / g] or more. The upper limit of AAP0.7 is not particularly limited, but in terms of the balance with other physical properties, it is preferably 35 [g / g] or less, more preferably 30 [g / g] or less, and even more preferably 28 [g / g] or less.
[0063] (5-3) Weight average particle diameter (D50), PSD (particle size distribution) NWSP 220.0.R2(15) The weight average particle diameter (D50) of the waste liquid solidifying agent of the present invention is 200 to 600 μm, preferably 250 to 500 μm, more preferably 280 to 500 μm, and even more preferably 300 to 450 μm. Also, the amount of fine particles (fine powder of water-absorbent resin) passing through a sieve with a mesh size of 150 μm (JIS standard sieve) is preferably 0 to 25% by weight, more preferably 0 to 15% by weight, and even more preferably 0 to 10% by weight, based on the total. Also, the amount of large particles that do not pass through a mesh size of 850 μm or more (or 710 μm or more) (JIS standard sieve) is preferably 0 to 3% by weight, more preferably 0 to 1% by weight, and even more preferably 0% by weight, based on the total water-absorbent resin particles.
[0064] In the present invention, the ratio of particles having a particle diameter of 150 μm or more and less than 850 μm, and further the ratio of particles having a particle diameter of 150 μm or more and less than 710 μm, is adjusted to preferably 80% by weight or more, more preferably 90% by weight or more (upper limit is 100% by weight) with respect to the entire water absorbent resin powder. Furthermore, the logarithmic standard deviation (σζ) of the particle size distribution is preferably 0.20 to 0.50, more preferably 0.25 to 0.50, even more preferably 0.25 to 0.45, and particularly preferably 0.30 to 0.40. These particle sizes can be measured by the same method as "(1) Average Particle Diameter and Distribution of Particle Diameter" described in European Patent No. 0349240, page 7, lines 25 to 43.
[0065] (5-4) Vortex The absorption speed (Vortex) of the waste liquid solidification agent of the present invention is preferably 60 seconds or less, 50 seconds or less, 40 seconds or less, or 30 seconds or less. Note that Vortex is defined as the absorption time for a 0.9% aqueous sodium chloride solution at a liquid temperature of 30°C in accordance with the water absorption speed test method for superabsorbent resins described in JIS K7224.
[0066] (5-5) "Moisture Content" (NWSP230.0.R2(15)) "Moisture Content" means the moisture content of the water absorbent resin, and specifically, it is a value (unit: mass%) calculated from the drying loss when 1 g of the waste liquid solidifying agent is dried at 105°C for 3 hours. The drying temperature may be changed to 180°C. The moisture content of the surface cross-linked water absorbent resin powder, the water absorbent resin composition, and the waste liquid solidifying agent made of the water absorbent resin composition of the present invention is 0% to 20%, more preferably 1% to 10%, under the measurement condition where the drying temperature is changed to 180°C per 1 g.
[0067] (5-6) More suitable physical properties The waste liquid solidifying agent of the present invention preferably contains, as a main component, a water-absorbent resin powder having a centrifugal retention capacity (CRC) of 25 to 50 g / g, an absorption capacity under pressure (AAP0.3) of 15 to 40 g / g, an absorption capacity under pressure (AAP0.7) of 10 to 35 g / g, an absorption speed (Vortex) of 60 seconds or less, and a weight average particle diameter (D50) of 200 to 600 μm, and further satisfies the above-mentioned ranges.
[0068] (6) Solidification performance of waste liquid solidification agent containing water-absorbing resin composition In order to achieve the object of the present invention, it is preferable that the waste liquid solidifying agent containing the water-absorbing resin composition of the present invention further satisfies the following physical properties.
[0069] (6-1) Settling rate of waste liquid solidification agent It is preferable that the waste liquid solidification agent of the present invention has a settling rate of 80% or more 30 seconds after 33 g of the waste liquid solidification agent is added to 1000 ml of 0.9% aqueous sodium chloride solution (23±1°C, more preferably 23±0.5°C) in a 1000 ml measuring cylinder (outer diameter 70 mm).
[0070] The floating and sinking states are determined by pouring 33 g of waste liquid solidification agent all at once into a measuring cylinder with an effective volume of 1000 ml (outer diameter 70 mm) placed with its axis oriented vertically (mounted on a horizontal stand) containing 1000 ml of 0.90% by weight sodium chloride aqueous solution at 23±1°C, and then determining the state 30 seconds later; waste liquid solidification agent present above the 500 ml position in the measuring cylinder is considered to be in a floating state, and waste liquid solidification agent present below the 500 ml position is considered to be in a sinking state.
[0071] The settling rate of the waste liquid solidification agent of the present invention may be evaluated by the method described in the Examples, but it is preferably more than 80% by mass to 100% by mass of the waste liquid solidification agent added, and more preferably the range is more than 85% by mass, more than 90% by mass, more than 95% by mass, and more than 98% by mass in that order.
[0072] (6-2) Gelation time of waste liquid solidification agent The gelation time of the waste liquid solidifying agent of the present invention may be specifically evaluated by the method described in the Examples, but is defined as the gelation time (time until the waste liquid solidifying agent completely absorbs the liquid) after 33 g of the waste liquid solidifying agent is added to 1000 ml of 0.9 mass % sodium chloride aqueous solution (23 ± 1 ° C, more preferably 23 ± 0.5 ° C) in a 1000 ml measuring cylinder (outer diameter 70 mm) placed on a horizontal stand, and is preferably within 15 minutes, more preferably within 13 minutes, and even more preferably within 10 minutes. If the gelation time exceeds 15 minutes, it may cause inconvenience in practical use, and may even fail to gel.
[0073] (6-3) Gel fluidity of waste liquid solidification agent The gel fluidity of the waste liquid solidifying agent of the present invention may be specifically evaluated by the method described in the Examples, and is defined as the gel fluidity 15 minutes after 33 g of the waste liquid solidifying agent is poured into 1000 ml of 0.9% by mass physiological saline (23±1°C, more preferably 23±0.5°C) in a 1000 ml measuring cylinder (outer diameter 70 mm) placed on a horizontal stand. More specifically, as shown in FIG. 1, the 1000 ml measuring cylinder is tilted 45°, and the gel fluidity is defined as the movement distance of the swollen gel (distance along the measuring cylinder, mm) 30 seconds later. The gel fluidity is preferably 0 to 5 mm. More preferably, it is within 3 mm, and most preferably within 1 mm.
[0074] (6-4) Ratio of upper and lower gel magnifications of waste liquid solidification agent The ratio of the upper and lower gel magnifications of the waste liquid solidifying agent of the present invention is preferably within 2 times. The ratio of the upper and lower gel magnifications may be specifically evaluated by the method described in the Examples, but as shown in Figure 2, 33 g of the waste liquid solidifying agent is added to 1000 ml of 0.9 mass% sodium chloride aqueous solution (23 ± 1 ° C, more preferably 23 ± 0.5 ° C) in a 1000 ml measuring cylinder (outer diameter 70 mm) placed on a horizontal stand, and the ratio is defined as the ratio of the upper and lower gel magnifications after gelation. The ratio of the upper and lower gel magnifications after gelation is defined as the ratio of the absorption magnification of the swollen gel present in the topmost layer of about 200 ml of the 1000 ml measuring cylinder to the swollen gel present in the bottommost layer of about 200 ml, and specifically can be calculated by the following formula. Upper and lower gel swelling ratio = Upper gel swelling ratio / Lower gel swelling ratio
[0075] The preferable range of the ratio of the upper and lower gel magnifications after gelation is within 5 times, more preferably within 4 times, 3 times, 2 times, 1.8 times, 1.6 times, 1.4 times, 1.2 times, and particularly preferably within 1.1 times. When the upper and lower gel magnifications exceed 5.0 times, the water absorbent resin is distributed non-uniformly, and there is a risk that the waste liquid will not be solidified in the portion where the water absorbent resin concentration is low, and it becomes necessary to add an additional waste liquid solidifying agent.
[0076] (7) Waste liquid The waste liquid that can be solidified (gelled, absorbs all the fluid liquid, and turns into a gel state without fluidity) by the waste liquid solidifying agent of the present invention is not particularly limited as long as the water absorbent resin can swell and gel, and is a liquid that is intended to be disposed of, and is a waste liquid that contains water as the main component, various components in blood, solvents other than water, inorganic salts, organic substances, etc. The water content in the waste liquid is sufficient to be 50% by weight or more, and preferably 60% by weight or more, 70% by weight or more, or 80% by weight or more is water. Note that water refers to the total amount of water contained in the waste liquid, such as water in blood, water contained in wastewater or sludge, water in urine, etc. The temperature of the waste liquid is not particularly limited as long as it is liquid, but it is usually about room temperature.
[0077] Examples of waste liquid include industrial waste liquid, waste liquid generated in food processing such as meat and fish, feces and urine waste liquid, radioactive waste liquid, beverage waste liquid, bodily fluid waste liquid such as urine and phlegm, muddy water containing sludge, medical waste liquid containing amniotic fluid and blood discharged during dental clinic treatment, hospital surgery, treatment, and childbirth, etc., and the like. The solidification of medical waste liquid is preferable. Furthermore, it can be suitably used for solidification of medical waste liquid containing blood. After collecting these in a container for safe disposal, they are incinerated or treated with chemicals and then treated in a septic tank.
[0078] (8) Method of solidifying and disposing of waste liquid using a waste liquid solidifying agent The waste liquid solidification method of the present invention is a method for treating waste liquid in which a treating agent is added to the waste liquid to solidify the waste liquid into a gel state, and the waste liquid solidification agent of the present invention described above is used as the treating agent. The waste liquid solidification agent of the present invention can be used to solidify various waste liquids such as beverage waste liquid, industrial waste liquid, and radioactive waste liquid, and may contain organic matter or solid dispersions. Due to its rapid and uniform solidification, it is preferably used to solidify medical waste liquid, which has many problems in the past. The waste liquid refers to an aqueous liquid to be disposed of or a filtered aqueous liquid. The aqueous liquid is, for example, as described above.
[0079] In the solidification method of the present invention, various container shapes (vertical, horizontal, etc.) for containing or storing waste liquid and methods for adding the solidifying agent (lump / divided addition to waste liquid, front / back addition to waste liquid) can be widely applied. In addition, when solidifying leaked waste liquid, the waste liquid solidifying agent of the present invention can be sprayed on the leaked aqueous liquid to solidify it. The waste liquid solidifying agent of the present invention is preferably used for solidifying waste liquid in a vertically long container (a container in the shape of a graduated cylinder) because of its rapid and uniform solidification. As a vertically long container, the height of the container is preferably 10 cm or more, or even 20 cm or more, and the ratio of the height to the diameter of the bottom is preferably 1.5 times or more, or even 5 times or more (if the bottom of the container is not circular, the area is converted to the diameter of the circle).
[0080] The waste liquid solidifying agent may be added directly in powder form, or may be added in a water-soluble, water-destructible or water-permeable container or bag. The waste liquid solidified by the method of the present invention may be removed from the container, but it is preferable to dispose of the entire container containing the waste liquid (in the case of multiple containers, only the inner container in contact with the waste liquid) in order to process it hygienically.
[0081] (9) Waste liquid solidification agent package containing waste liquid solidification agent The waste liquid solidification package of the present invention is a package for introducing a waste liquid solidification agent, which is packaged in a water-insoluble container having an outlet, into waste liquid. When solidifying waste liquid, the outlet can be opened and the powdered waste liquid solidification agent can be introduced into the container containing the waste liquid.
[0082] In the package of the present invention, the shape and material of the container and packaging material used to package the waste liquid solidification material are not particularly limited, and any water-insoluble packaging material may be used. The size of the package container is preferably one that can seal 10 to 1,000 g of the waste liquid solidification material and can be partially opened to take out the waste liquid solidification material therefrom, such as a wide-mouthed plastic bottle, a narrow-mouthed plastic bottle, a bag made of polyethylene, a bag made of polypropylene, etc.
[0083] As described above, the waste liquid solidifying agent of the present invention is preferably used as a waste liquid solidifying agent for treating medical waste liquid containing blood. The present invention also includes a waste liquid solidifying method using a waste liquid solidifying agent. As a method for solidifying a waste liquid, for example, the waste liquid solidifying agent of the present invention may be added to a container containing the waste liquid. Also, a waste liquid may be added to a container containing the waste liquid solidifying agent. An example of the waste liquid in such a method for solidifying a waste liquid is a medical waste liquid containing blood. Furthermore, the present invention also includes a method for disposing of a waste liquid. For example, the waste liquid solidified by the above-mentioned method for solidifying a waste liquid may be disposed of together with the container. The present invention also includes a waste liquid solidifying agent package, and the above-mentioned waste liquid solidifying agent may be packaged in a water-insoluble container having an outlet.
[0084] This application claims the benefit of priority based on Japanese Patent Application No. 2019-030680, filed on February 22, 2019. The entire content of the specification of Japanese Patent Application No. 2019-030680, filed on February 22, 2019, is incorporated herein by reference. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples as long as it does not deviate from the gist of the invention. Note that the physical properties in the examples are measured in accordance with EDANA NONWOVENS STANDARD PROCEDURES (2015) in Non-Patent Document 3 and Patent Document 8, and the physical properties not specified in EDANA are measured based on the descriptions in (1) to (4) below.
[0086] (1) Gel time The gelation time of the waste liquid solidification agent in this example was defined as the gelation time after 33 g of the waste liquid solidification agent was added to 1000 ml of 0.9 mass % sodium chloride aqueous solution (23±1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm).
[0087] Specifically, the gelation time was measured (solidification test) by the following method. A measuring cylinder (outer diameter 70 mm, height 420 mm, manufactured by SIBATA, listed in the General Catalog of Physical and Chemical Research Equipment 2015, A-7000, code No. 9189-11) with an effective volume of 1000 ml placed on a horizontal stand containing 1000 ml of 0.9% by mass sodium chloride aqueous solution was installed with an apparent density measuring funnel described in JIS K3362 at the top so that the height of the lower opening from the liquid surface was 40 mm. With the lower opening of the funnel open, 33 g of waste liquid solidifying agent was gently placed in the funnel, and the time until the 0.9% sodium chloride aqueous solution was completely absorbed was defined as the gelation time. The temperature of the sodium chloride aqueous solution during the measurement was 23±1°C.
[0088] (2) Settling rate of solidifying agent The settling rate of the waste liquid solidifying agent in this example was defined as the settling rate 30 seconds after 33 g of the waste liquid solidifying agent was added to 1000 ml of 0.9% sodium chloride aqueous solution (23±1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm).
[0089] In the solidification test of (1) above, 30 seconds after the waste liquid solidification agent was added, the upper 500 ml and the lower 500 ml of a measuring cylinder containing 1000 ml of 0.9% sodium chloride aqueous solution were taken out, and the waste liquid solidification agent and its swollen gel were filtered through the JIS 45 μm mesh sieve (inner diameter 300 mm).Then, the JIS 45 μm mesh sieve (inner diameter 300 mm) was dried with hot air at 180°C for 16 hours to obtain the solid weight derived from the waste liquid solidification agent, and the weight ratio (solidification agent sedimentation rate) of the waste liquid solidification agent floating in the upper layer and the waste liquid solidification agent 33 g settling in the lower layer was calculated from the following formula (1). Solidification agent settling rate (%) = weight of solids in the lower 500 mL layer (g) / 33 (g) x 100 (Equation 1) In addition, if the entire amount of waste liquid solidification agent is visually confirmed to have settled 30 seconds after addition of the agent, the amount may be regarded as 100%.
[0090] (3) Gel fluidity The gel fluidity of the waste liquid solidification agent in this example was defined as the gel fluidity 15 minutes after 33 g of the waste liquid solidification agent was added to 1000 ml of 0.9% saline (23±1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm).
[0091] Using the same method as in the solidification test (1) above, a 0.9% sodium chloride aqueous solution was solidified using the waste liquid solidification agent, and 15 minutes after the waste liquid solidification agent was added, the swollen gel in a 1000 ml measuring cylinder was tilted 45° and left to stand for 30 seconds, and the movement distance (mm) of the swollen gel was measured. The movement distance was measured along the measuring cylinder as shown in Figure 1.
[0092] (4) Ratio of upper and lower gel magnifications The upper and lower gel magnification ratio of the waste liquid solidifying agent in this example was determined by adding 33 g of the waste liquid solidifying agent to 1000 ml of 0.9 mass % sodium chloride aqueous solution (23 ± 1 ° C.) in a 1000 ml measuring cylinder (outer diameter 70 mm) and determining the upper and lower gel magnification ratio after gelation. The upper and lower gel magnification ratio was determined by the ratio of the absorption magnification of the swollen gel present in the topmost 200 ml portion of the 1000 ml measuring cylinder to the bottommost 200 ml portion.
[0093] In the same manner as in the solidification test (1) above, a 0.9% by mass sodium chloride aqueous solution was solidified using a waste liquid solidification agent, and then 15 minutes after the waste liquid solidification agent was added, the contents (swollen gel) at the 800-1000 ml position (top layer) of the 1000 ml measuring cylinder were all removed and the mass WA (g) was measured. This was transferred to a stainless steel tray and dried with hot air at 180°C for 16 hours, and then cooled to room temperature, after which the mass WB (g) after drying was measured, and the swelling ratio of the top layer gel was calculated using the following formula (2). Upper gel swelling ratio [g / g]=WA / WB (Equation 2) The lower layer gel swelling ratio was also determined for the contents (swollen gel) at the 0 to 200 ml positions (bottom layer) of the 1000 ml graduated cylinder in the same manner. From these, the upper and lower gel swelling ratios were calculated according to the following formula (3). Upper and lower gel swelling ratio = Upper gel swelling ratio / Lower gel swelling ratio (Equation 3)
[0094] (5)Solidification test by adding waste liquid solidification agent In the gelation time measurement (solidification test) of the above (1), a similar operation was carried out using a simulated waste liquid (0.9% by weight sodium chloride aqueous solution: carboxymethylcellulose: glycerin = 94.75 parts by weight: 0.25 parts by weight: 5 parts by weight) instead of the 0.9% by weight sodium chloride aqueous solution. However, if gelation was not completed after 15 minutes, 33 g of the waste liquid solidification agent was further added, and the gelation time was continued to be measured.
[0095] [Production Example 1] 351g of acrylic acid, 0.76g of polyethylene glycol diacrylate (molecular weight 522.66, average number of ethylene oxide units; n=9), 21.50g of 0.1% by weight aqueous solution of trisodium diethylenetriaminepentaacetate, 296g of 48.5% by weight aqueous solution of sodium hydroxide, and 316g of ion-exchanged water were added to a 1L polypropylene container and stirred to mix. The mixture obtained by this operation was designated as aqueous monomer solution (a). The temperature of the aqueous monomer solution (a) rose to about 80°C due to heat of neutralization. Stirring was continued thereafter, and when the temperature of the aqueous monomer solution (a) reached 78°C, 15.4g of aqueous 3.8% by weight aqueous sodium persulfate solution was added to obtain reaction solution (a). The reaction solution (a) was immediately poured into a stainless steel vat-type reactor (bottom: 340×340 mm, height: 25 mm, inner surface: Teflon (registered trademark) coating) in an open-air system, and the polymerization reaction started immediately. The surface temperature of the stainless steel vat-type reactor was preset to 50° C. using a hot plate (NEO HOTPLATE HI-1000 / Iuchi Seiei-do Co., Ltd.).
[0096] The polymerization reaction proceeded by expanding and foaming in all directions toward the top of the vat-type reactor while generating steam, and then contracted to a size slightly larger than the bottom of the reactor. The polymer obtained by this operation was a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") (a). The polymerization reaction (expansion and contraction) was completed in about 1 minute, but the hydrogel (a) was held in the reactor for 3 minutes thereafter. This series of operations was carried out in a system open to the atmosphere.
[0097] Next, the obtained hydrous gel (a) was gel-pulverized using a meat chopper (No. 32 type / manufactured by Hiraga Manufacturing Co., Ltd.) equipped with a die having a die hole diameter of 9.5 mm to obtain a particulate hydrous gel (a). The gel was pulverized by feeding 2.4 (kg / min) of hydrous gel (a) and 5.0 (kg / h) of steam into the meat chopper with the screw shaft rotation speed of the meat chopper set to 130 rpm. Next, the particulate hydrous gel (a) obtained by the gel pulverization was spread on a stainless steel wire mesh with an opening of 850 μm, heated and dried at 180 ° C. for 30 minutes using a hot air dryer, and then pulverized using a roll mill (WML type roll pulverizer / manufactured by Inokuchi Giken Co., Ltd.) and classified using JIS standard sieves with openings of 850 μm and 150 μm. This series of operations resulted in the production of a water-absorbent resin powder (a) that is an amorphous crushed water-absorbent resin (water content of 4.9% by mass). The water absorbent resin powder (a) had a CRC (absorbency under no load) of 47.9 [g / g].
[0098] [Production Example 2] The water absorbent resin powder (a) obtained in the above Production Example 1 was transferred to a rotary mixer manufactured by Lödige AG, Germany, and a surface cross-linking agent aqueous solution consisting of 0.03 parts by weight of ethylene glycol diglycidyl ether, 1.5 parts by weight of propylene glycol, and 3.5 parts by weight of water was uniformly mixed with 100 parts by weight of the water absorbent resin powder (a), and heat-treated at 100°C for 40 minutes. Thereafter, the mixture was passed through a JIS standard sieve with an opening of 850 μm to obtain a water absorbent resin (surface cross-linked water absorbent resin powder) (A) having a water content of 7.8%. The water absorbent resin (A) was amorphous, and 95% by weight or more was contained in the range of 150 μm or more and less than 850 μm. The CRC (absorption capacity without pressure) of the water absorbent resin powder (a) was 35.6 [g / g].
[0099] [Example 1] 0.3 mass % (solid content 30%) of colloidal silica (Klebosol30CAL25, particle size 25 μm; manufactured by Merck) was mixed as a cationic additive with 100 parts by weight of the surface-crosslinked water absorbent resin (A) obtained in the above-mentioned Production Example 2. The mixing was carried out by putting 30 g of the surface-crosslinked water absorbent resin (A) into a 225 mL mayonnaise bottle together with the colloidal silica, and shaking the mixture for 3 minutes using a paint shaker (manufactured by Toyo Seiki Co., Ltd.), to obtain a waste liquid solidifying agent (1) made of a water absorbent resin composition containing cationic colloidal silica (0.09 mass % of the water absorbent resin in terms of solid content) on the surface of the surface-crosslinked water absorbent resin (A). The waste liquid solidifying agent (1) had CRC=35.3 [g / g], AAP0.3=31.9 [g / g], AAP0.7=23.0 [g / g], vortex=42 [sec], and D50=360 [μm]. The settling rate of the waste liquid solidification agent (1) was measured and found to be 100%.
[0100] [Example 2] In the above Example 1, 0.3 mass% of colloidal silica was replaced with 0.3 mass% of hydrotalcite (DHT-6, particle size 0.5 μm; manufactured by Kyowa Chemical Industry Co., Ltd.) as a cationic additive, and the same operation was performed to obtain a waste liquid solidification agent (2) consisting of a water absorbent resin composition containing hydrotalcite on the surface of a surface cross-linked water absorbent resin (A). The waste liquid solidification agent (2) had CRC=35.6[g / g], AAP0.3=31.2[g / g], AAP0.7=22.4[g / g], vortex=40[sec], and D50=350[μm]. The solidification agent sedimentation rate of the waste liquid solidification agent (2) was measured and found to be 100%.
[0101] [Example 3] In the above Example 1, 0.3 mass% of colloidal silica was replaced with 0.3 mass% of zeolite (Y type, HSZ-360CHUA, average particle size 6.0 μm; manufactured by Tosoh Corporation), and the same operation was performed to obtain a waste liquid solidification agent (3) made of a water absorbent resin composition containing zeolite on the surface of a surface cross-linked water absorbent resin (A). The waste liquid solidification agent (3) had CRC = 35.3 [g / g], AAP0.3 = 31.1 [g / g], AAP0.7 = 21.3 [g / g], vortex = 44 [sec], and D50 = 345 [μm]. The solidification agent sedimentation rate of the waste liquid solidification agent (3) was measured and was 100%.
[0102] [Comparative Example 1] The surface-crosslinked water absorbent resin (A) obtained in the above Production Example 2 was used as it was as a comparative waste liquid solidifying agent (1). The solidifying agent sedimentation rate of the comparative waste liquid solidifying agent (1) was measured and found to be 100%.
[0103] [Comparative Example 2] In the above Example 2, the same operation was carried out except that the surface-crosslinked water absorbent resin (A) was replaced with the water absorbent resin powder (a) (water absorbent resin powder not surface-crosslinked) of Production Example 1, to obtain a comparative waste liquid solidifying agent (2) made of a water absorbent resin composition containing hydrotalcite on the surface of the water absorbent resin (a). The solidifying agent sedimentation rate of the comparative waste liquid solidifying agent (2) was measured and found to be 100%.
[0104] [Comparative Example 3] In the above Example 1, 0.3 mass% of colloidal silica was replaced with 0.3 mass% of anionic additive montmorillonite (particle size 0.5 μm; manufactured by Alfa Aesar) to obtain a comparative waste liquid solidification agent (3) made of a water absorbent resin composition containing montmorillonite on the surface of a surface cross-linked water absorbent resin (A). The solidification agent sedimentation rate of the comparative waste liquid solidification agent (3) was measured and found to be 100%.
[0105] [Comparative Example 4] In the above Example 1, 0.3 mass% of colloidal silica was replaced with 0.3 mass% of kaolin (particle size 0.7 μm; manufactured by IMERYS) as a neutral additive, and the same operation was carried out to obtain a comparative waste liquid solidification agent (4) made of a water absorbent resin composition containing kaolin on the surface of a surface cross-linked water absorbent resin (A). The solidification agent sedimentation rate of the comparative waste liquid solidification agent (4) was measured and found to be 100%.
[0106] [Comparative Example 5] In the above Example 1, 0.3 mass% of colloidal silica was replaced with 0.3 mass% of talc (SG-2000, particle size 1.0 μm; manufactured by Nippon Talc Co., Ltd.) as a neutral additive, and the same operation was carried out to obtain a comparative waste liquid solidification agent (5) made of a water absorbent resin composition containing talc on the surface of a surface cross-linked water absorbent resin (A). The solidification agent sedimentation rate of the comparative waste liquid solidification agent (5) was measured and found to be 100%.
[0107] (Evaluation Results) The gelation time and gel fluidity of the sedimentation type waste liquid solidifying agents (1) to (3) and the comparative waste liquid solidifying agents (1) to (5) obtained above are shown in Table 1.
[0108] [Table 1]
[0109] [Comparative Example 6] For the surface-crosslinked water absorbent resin (A) obtained in the above Production Example 2, in accordance with Example 1 of Patent Document 8 (JP Patent Publication 2016-203106 A), 0.1 mass% of zinc stearate (Kanto Chemical Co., Ltd., Kaga Grade 1) was added to a Loedige mixer (Loedige, Type: M5R) at 25°C and a relative humidity of 50%RH with respect to 100 parts of the above surface-crosslinked water absorbent resin (A), and the mixture was stirred at 330 rpm for 90 seconds to obtain a comparative waste liquid solidification agent (6) consisting of a water absorbent resin composition containing zinc stearate on the surface of the water absorbent resin. The solidification agent sedimentation rate of the comparative waste liquid solidification agent (6) was measured and found to be 25%.
[0110] For the comparative waste liquid solidification agent (6), when a solidification test was carried out by adding additional waste liquid solidification agent (5), after adding 33 g of the comparative waste liquid solidification agent (6), some of the comparative waste liquid solidification agent (6) floated and some of it sank, and gelation proceeded from both the top and bottom of the waste liquid, but after 15 minutes, the center part 8 of the measuring cylinder had not gelled and excess liquid was observed, as shown in Figure 3. In order to gel the excess liquid, an additional 33 g of the comparative waste liquid solidification agent (6) was added, but the top part of the waste liquid had already gelled (solidified), and the additional comparative waste liquid solidification agent (6) could not reach the center part 8 of the measuring cylinder (Figure 3), and therefore could not solidify.
[0111] [Example 4] When the gelation time was measured for the waste liquid solidification agent (2) obtained in Example 2, after 33 g of the waste liquid solidification agent (2) was added, all of the waste liquid solidification agent (2) settled and gelation proceeded from the bottom of the waste liquid, but after 15 minutes, the top of the measuring cylinder (top 2 in Figure 3) had not gelled and excess liquid was observed. When an additional 33 g of the waste liquid solidification agent (2) was added in order to gel the excess liquid, all of the excess liquid was gelled after 30 seconds.
[0112] (summary) It was revealed that the waste liquid solidifying agents (1) to (3) solidify quickly and uniformly as sedimentation type waste liquid solidifying agents from their settling rates. The comparative waste liquid solidifying agents (1) to (5) are sedimentation type waste liquid solidifying agents from their settling rates, but it was revealed that the comparative waste liquid solidifying agents (1), (3), (4), and (5) do not contain a cationic additive, and the comparative waste liquid solidifying agent (2) does not have a surface cross-linked water absorbent resin powder, so rapid solidification or uniform solidification cannot be achieved. In addition, the comparative waste liquid solidifying agent (6) corresponding to Example 1 of Patent Document 8 is a floating type waste liquid solidifying agent from the measured settling rate, so it was shown that it is difficult to add the waste liquid solidifying agent appropriately according to the solidification amount.
[0113] As described above, the present invention provides a sedimentation type waste liquid solidification agent that can be easily added according to the concentration of the waste liquid. The present invention solves the above problems by using a cationic additive on the surface of a surface-crosslinked water-absorbent resin instead of the additives (surfactants, inorganic particles, chelating agents, nonionic water-absorbent resins, alkali-soluble resins, hydrophobic substances, etc.) of the conventional waste liquid solidification agents described in Patent Documents 1 to 13, and has found that a sedimentation type waste liquid solidification agent can be used for the first time to rapidly and uniformly gel the waste liquid, thereby completing the present invention.
[0114] The waste liquid solidifying agents of Patent Documents 1 to 13 and the like do not suggest a waste liquid solidifying agent consisting of a particulate water absorbent resin composition containing a surface-crosslinked water absorbent resin powder as a main component and further containing a water-insoluble cationic additive on the surface of the water absorbent resin powder. In addition, numerous uses for water in a broad sense, including the various uses described in Non-Patent Documents 1 and 2, have been proposed for the water absorbent resin, and the water absorbent resin is not limited to a simple water absorption function, and is required to have a number of various additional functions such as durability, urine resistance, gel strength, powder flowability, anti-caking property, liquid permeability, dust control property, deodorizing property, antibacterial property, decomposability at the time of disposal, impact resistance stability, and mixability in the manufacturing process, and many various additives have been proposed for this purpose. However, the conventional techniques of water absorbent resins, including those of Patent Documents 1 to 13, do not suggest that a water-insoluble cationic additive solves the above-mentioned problems of waste liquid solidifying agents in the numerous uses and numerous additives and additional functions of the water absorbent resin. [Industrial Applicability]
[0115] When waste liquid is solidified using the waste liquid solidifying agent of the present invention, the agent essentially settles, and solidification proceeds from the bottom of the waste liquid. Therefore, particularly when a container long in the vertical direction is used, the waste liquid solidifying agent can be added appropriately according to the amount of waste liquid to be solidified, and the waste liquid can be solidified at low cost using the minimum amount required. Therefore, the waste liquid solidifying agent of the present invention can be effectively used for solidifying various types of waste liquid such as beverage waste liquid, industrial waste liquid, radioactive waste liquid, feces and urine waste liquid, in particular waste liquid containing blood or body fluids. [Explanation of symbols]
[0116] 1 graduated cylinder 2. Swollen gel 3. Gel material at the 800-1000ml position (top layer) 4. Gel at 600~800ml 5 Gel at 400~600ml 6 Gel at 200~400ml 7 Gel matter at the 0-200ml position (approximately the bottom 200ml part) 8 Excess liquid (In the case of floating type waste liquid solidification agent, excess water is generated at the center part 8 in FIG. 3.)
Claims
1. A method for solidifying a waste liquid by using a waste liquid solidifying agent, which contains a water absorbent resin composition including (A) a surface-crosslinked water absorbent resin powder and (B) a water-insoluble cationic additive present on a surface of the water absorbent resin powder, and is used for gelling the waste liquid by precipitating the water absorbent resin composition in the waste liquid, The water-insoluble cationic additive is at least one water-insoluble inorganic compound selected from the group consisting of colloidal silica, hydrotalcite, and zeolite; The water absorbent resin composition contains 0.01 to 5 parts by weight of a water-insoluble cationic additive per 100 parts by weight of the surface-crosslinked water absorbent resin powder. A method for solidifying waste liquid using a waste liquid solidifying agent.
2. 2. The method for solidifying a waste liquid using a waste liquid solidifying agent according to claim 1, wherein the water-insoluble cationic additive is in the form of fine particles having a particle size of 50 μm or less.
3. Centrifuge retention capacity (CRC) of 25 to 50 g / g; Absorption capacity under pressure (AAP0.3) is 15 to 40 g / g, Absorption capacity under pressure (AAP 0.7) is 10 to 35 g / g, Absorption speed (Vortex) is 60 seconds or less, 3. The method for solidifying a waste liquid using the waste liquid solidifying agent according to claim 1 or 2, wherein the weight average particle diameter (D50) is 200 to 600 μm.
4. 4. The method for solidifying a waste liquid by using a waste liquid solidifying agent according to claim 1, wherein the surface-crosslinked water-absorbent resin powder mainly comprises a polyacrylic acid (salt)-based crosslinked polymer.
5. The method for solidifying a waste liquid using a waste liquid solidifying agent according to any one of claims 1 to 4, wherein a settling rate (mass ratio) of the waste liquid solidifying agent 30 seconds after 33 g of the waste liquid solidifying agent is added to 1000 ml of a 0.9% aqueous sodium chloride solution (23±1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm) is 80% or more.
6. The method for solidifying a waste liquid using the waste liquid solidifying agent according to any one of claims 1 to 5, wherein the gelation time after adding 33 g of the waste liquid solidifying agent to 1000 ml of 0.9% sodium chloride aqueous solution (23°C ± 1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm) is within 15 minutes.
7. 7. The method for solidifying waste liquid using the waste liquid solidifying agent according to any one of claims 1 to 6, wherein the gel fluidity is 0 to 5 mm 15 minutes after 33 g of the waste liquid solidifying agent is added to 1000 ml of 0.9% sodium chloride aqueous solution (23°C ± 1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm). The gel fluidity is defined as the distance (mm) traveled by the swollen gel after 30 seconds when a 1000 ml measuring cylinder is tilted at an angle of 45°.
8. A method for solidifying waste liquid using the waste liquid solidifying agent according to any one of claims 1 to 7, wherein the ratio of the upper and lower gel magnifications after gelation when 33 g of the waste liquid solidifying agent is added to 1000 ml of 0.9% sodium chloride aqueous solution (23°C ± 1°C) in a 1000 ml measuring cylinder (outer diameter 70 mm) calculated by the following formula is within 2 times. Upper and lower gel swelling ratio = upper gel swelling ratio / lower gel swelling ratio (In the formula, The upper layer gel swelling ratio and the lower layer gel swelling ratio are values obtained based on the following formula. Upper layer gel swelling ratio [g / g] = WA / WB In the formula, WA (g) is the mass measured by removing all of the contents (swollen gel) from the 800 to 1000 ml position (top layer) of the 1000 ml measuring cylinder 15 minutes after solidifying a 0.9% by mass sodium chloride aqueous solution using a waste liquid solidifying agent and then adding the waste liquid solidifying agent. WB (g) is the mass of the swollen gel after the above WA (g) measurement, which is transferred to a stainless steel tray, dried with hot air at 180° C. for 16 hours, cooled to room temperature, and then dried, and then measured. Lower layer gel swelling ratio [g / g]=WA / WB In the formula, WA(g) is the mass of the swollen gel taken out from the 80-200 ml position (bottom layer) of the 1000 ml measuring cylinder 15 minutes after solidifying a 0.9% by mass sodium chloride aqueous solution using a waste liquid solidifying agent and then measuring the mass. WB(g) is the mass of the swollen gel after measuring WA(g) by transferring it to a stainless steel tray, drying it with hot air at 180°C for 16 hours, cooling it to room temperature, and then drying it.
9. 9. A method for solidifying a waste liquid using the waste liquid solidifying agent according to claim 1, further comprising a water-soluble polyvalent metal cationic additive having a solubility in water of 10 g / 100 g or more.
10. The method for solidifying a waste liquid according to any one of claims 1 to 9, further comprising adding a waste liquid solidifying agent to a vessel containing the waste liquid.
11. 10. The method for solidifying a waste liquid according to claim 1, wherein the waste liquid is added to a vessel containing a waste liquid solidifying agent.
12. 12. The method for solidifying a waste liquid according to claim 1, wherein the waste liquid is a medical waste liquid containing blood.
13. A method for disposing of waste liquid, further comprising disposing of the waste liquid solidified by the method for solidifying waste liquid according to any one of claims 1 to 12 together with the container.
14. 12. The method for solidifying a waste liquid according to claim 10 or 11, wherein the container containing the waste liquid and / or the container containing the waste liquid solidifying agent is elongated in a height direction of the container.
Citation Information
Patent Citations
Material and method for dental waste water treatment
JP1992235783A
Gelating material for medical waste and method of gelation
JP1994000216A
Treating agent of waste operation liquid and treatment
JP1996047637A
Medical waste water treatment agent
JP1999169451A
Method for manufacturing modified highly-water- absorptive resin
JP2001137704A
